Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2000
DOI: 10.1007/s001980070034
|View full text |Cite
|
Sign up to set email alerts
|

Metacarpal Morphometry Using a Semi-automated Technique in the Assessment of Osteoporosis and Vertebral Fracture Risk

Abstract: Metacarpal morphometry represents a potentially cheap and widely available non-invasive assessment of skeletal status. In two cross-sectional studies, we compared the performance characteristics of a semiautomated technique (the Teijin Bonalyzer) with an in-house manual measurement, and with measures of skeletal strength at other sites. The metacarpal cortical index (mCI) was measured on hand radiographs of 178 osteoporotic women using both the Teijin Bonalyzer and a digitizing tablet. Measurements on the latt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 12 publications
(16 reference statements)
0
24
0
2
Order By: Relevance
“…Therefore, theoretically, these measurements may not be useful for prediction of fracture risk at clinically relevant sites. However, previous retrospective studies found that radiogrammetry measurements of the metacarpals and radius are lower in individuals with prevalent vertebral and wrist fractures [9,[13][14][15][16]. In addition, both retrospective and prospective studies demonstrated an association between BMD of the phalanges computed using radiographic absorptiometry and fracture risk [38][39][40].…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…Therefore, theoretically, these measurements may not be useful for prediction of fracture risk at clinically relevant sites. However, previous retrospective studies found that radiogrammetry measurements of the metacarpals and radius are lower in individuals with prevalent vertebral and wrist fractures [9,[13][14][15][16]. In addition, both retrospective and prospective studies demonstrated an association between BMD of the phalanges computed using radiographic absorptiometry and fracture risk [38][39][40].…”
Section: Discussionmentioning
confidence: 96%
“…Radiogrammetry has potential to be useful for diagnosis of osteoporosis, as previous studies have shown that ageand menopause-related decreases in radiogrammetry measurements are similar to the observed decrements in bone mineral density (BMD) [9][10][11][12]. In addition, radiogrammetry measurements of the metacarpals and radius are associated with prevalent wrist and vertebral fractures [9,[13][14][15][16]. One major advantage to radiogrammetry measurements is that they can be performed on standard radiographs of the hand and forearm, thereby giving the procedure the potential to be widely available.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…Dey et al. 33 found significant correlations between total hip BMD and the metacarpal index ( r = 0.48, P < 0.001) when screening for osteoporosis in 379 elderly, community‐dwelling women aged 75 years and older. A comparison of our results with those of previous studies indicated that our CAD system might be a useful screening tool for osteoporosis.…”
Section: Discussionmentioning
confidence: 99%